Continuing training of non-university teachers: An analysis of impressions, preferences, and needs - María José Mayorga Fernández; Inmaculada Martínez García; Fabián Núñez Avilés (Revista Española de Pedagogía)
Continuing training is a key component in teachers’ professional development as it enables them to meet the educational needs of the knowledge society and contribute to a quality educational system. This research aims to identify the training needs and preferences of in-service teachers and their impressions of the continuing training they receive. To do so, a quantitative study with a descriptive and correlative ex-post facto design was used. A total of 801 non-university teachers from schools in the autonomous community of Andalusia participated in the research. The data were collected using a questionnaire with an ad hoc design, taking as reference the instrument developed by Sangrà et al. (2019). For the data analysis, an exploratory factor analysis was performed giving 9 dimensions. The correlations between them were calculated and the non-parametric Mann-Whitney test was used to compare differences in means by gender. The results show that teachers are motivated for teacher training as they see that it is linked to improvements in their professional practice and in student results, and that they prefer formal training activities. The content they prefer relates to school development, entrepreneurial skills and their transfer, innovative teaching methodologies, didactic updating, and ICT. Some gender differences in training preferences were found, although the total score is similar for men and women, with women wanting more training in four of the dimensions and being more motivated to participate in such training.